Comprehensive approaches reveal key transcripts and metabolites highlighting metabolic diversity among three oriental tobacco varieties - Tsaballa, Aphrodite; Sarrou, Eirini; Xanthopoulou, Aliki; Tsaliki, Eleni; Kissoudis, Christos; Karagiannis, Evangelos; Michailidis, Michail; Martens, Stefan; Sperdouli, Elektra; Hilioti, Zoe; Fotopoulos, Vasileios; Nianiou-Obeidat, Irini; et al. (My University, 2020)
Tobacco is an economically important crop with leaves that are a significant source of aromatic, bioactive compounds such as phenolics and alkaloids. In the present study un-biased transcriptomics and metabolomics approaches were employed to identify and quantify individual changes in transcript and metabolite profiles in leaves of three oriental tobacco varieties. Based on next generation sequencing (NGS) and gas chromatography mass spectrometry (GC–MS) technologies, a wide variety of transcripts and metabolites was detected and the metabolic diversity among varieties was determined. Genes with largest expression differences were identified in the leaves of the three varieties; among them three were commonly over-expressed in two varieties in comparison with the third variety. Notably, significant expression differences were recorded in phenylalanine ammonia lyase (PAL) genes that are key genes of phenylpropanoid biosynthesis. Following transcriptomics, metabolomics analysis has shown that polyphenolic compounds varied widely among the three varieties. Furthermore, statistically significant differences in soluble sugars, alcohols, organic acids, amino acids and other metabolites were also revealed. The integration of the two -omics datasets in determining diversity of tobacco varieties offers important readouts for the genetic control of metabolite production and constitutes a resource for future studies in the area of plant biotechnology for improving tobacco specific traits.
Keywords: N. tabacum; RNA-seq; Leaf transcriptomics; GC–MS; Metabolomics